Tuning dynamic DNA- and peptide-driven self-assembly in DNA–peptide conjugates. Issue 1 (6th December 2022) - Taylor, Emerald R.; Sato, Akiko; Jones, Isobel; Gudeangadi, Prashant G.; Beal, David M.; Hopper, James A.; Xue, Wei-Feng; Reithofer, Michael R.; Serpell, Christopher J.
Abstract : DNA and peptide nanotechnologies can be interfaced to create hierarchical and emergent superstructures, which evolve with time. Abstract : DNA–peptide conjugates offer an opportunity to marry the benefits of both biomolecular classes, combining the high level of programmability found with DNA, with the chemical diversity of peptides. These hybrid systems offer potential in fields such as therapeutics, nanotechnology, and robotics. Using the first DNA–β-turn peptide conjugate, we present three studies investigating the self-assembly of DNA–peptide conjugates over a period of 28 days. Time-course studies, such as these have not been previously conducted for DNA–peptide conjugates, although they are common in pure peptide assembly, for example in amyloid research. By using aging studies to assess the structures produced, we gain insights into the dynamic nature of these systems. The first study explores the influence varying amounts of DNA–peptide conjugates have on the self-assembly of our parent peptide. Study 2 explores how DNA and peptide can work together to change the structures observed during aging. Study 3 investigates the presence of orthogonality within our system by switching the DNA and peptide control on and off independently. These results show that two orthogonal self-assemblies can be combined and operated independently or in tandem within a single macromolecule, with both spatial and temporal effects upon the resultant nanostructures.